Some ascidians from the southern coast of Madagascar collected during the “AtimoVatae” survey - Monniot, Françoise (Zootaxa, 2012)
Surveys of littoral invertebrates along the southern coast of Madagascar have produced the first study of ascidians in this part of the Indian Ocean. Collections were made by SCUBA divers in May and June 2010 down to 25m depth. This region is considered the southern limit for coral reefs but remains diverse biologically. Upwellings and an abundant plankton community particularly favour the abundance of ascidians in this area. Of the 39 species of non-didemnid species described here, eight are new. Ten species are common to South Africa. Other species were for the most part already known from the Mozambique Channel and a few have also been recorded in the western Pacific (either cosmopolitan or introduced).